Novel prospective umbrella‐type lung cancer registry study for clarifying clinical practice patterns: CS‐Lung‐003 study protocol. Issue 5 (12th January 2021) - Nishii, Kazuya; Inoue, Masaaki; Obata, Hideto; Ueda, Yutaka; Kozuki, Toshiyuki; Yamasaki, Masahiro; Moritaka, Tomonori; Awaya, Yoshikazu; Sugimoto, Keisuke; Gemba, Kenichi; Kuyama, Shoichi; Ichikawa, Hirohisa; et al.
Abstract: Introduction: Conventional cancer registries are suitable for simple surveillance of cancer patients, including disease frequency and distribution, demographics, and prognosis; however, the collected data are inadequate to clarify comprehensively diverse clinical questions in daily practice. Methods: We constructed an umbrella‐type lung cancer patient registry (CS‐Lung‐003) integrating multiple related prospective observational studies (linked studies) that reflect clinical questions about lung cancer treatment. The primary endpoint of this registry is to clarify daily clinical practice patterns in lung cancer treatment; a key inclusion criterion is pathologically diagnosed lung cancer. Under this registry, indispensable clinical items are detected in advance across all active linked studies and gathered prospectively and systematically to avoid excessive or insufficient data collection. Researchers are to input information mutually, irrespective of the relevance to each researcher's own study. Linked studies under the umbrella of the CS‐Lung‐003 registry will be updated annually with newly raised clinical questions; some linked studies will be newly created, while others will be deleted after the completion of the analysis. Enrollment began in July 2017. Discussion: We successfully launched the umbrella‐type CS‐Lung‐003 registry. Under this single registry, researchers collaborate on patient registration and data provision for their own and other studies. Thus, the registry will produce results for multiple domains of study, providing answers to questions about lung cancer treatment raised by other researchers. Through such analysis of each linked study, this registry will contribute to the comprehensive elucidation of actual daily practice patterns in lung cancer treatment. Key points: CS‐Lung‐003 registry directly integrates multiple linked studies created under the umbrella of this cancer registry to solve various clinical questions regarding daily practice patterns of lung cancer treatment. Abstract : We constructed an umbrella‐type lung cancer patient registry (CS‐Lung‐003) integrating multiple related prospective observational studies (linked studies) that reflect clinical questions about lung cancer treatment. Under this single registry, researchers collaborate on patient registration and data provision for their own and other studies.